Character: Sofía Enviales Mejía (2009)
Sofía has a particular, mischievous and happy smile. She is part of the hotbeds of research for school students and participated in the first stage of EAFIT Children's University last year. "She is a very good friend, she is very dear, knows how to share, treats people well, accepts them as they are," says Ana María Iglesias, a friend of Sofía since they were in group 1 and who this year was her partner in the hotbed of Physics.